A comparative study of psychiatric comorbidities and quality of life in patients with epilepsy and psychogenic non-epileptic seizures - Mandal, Mahadeb; Durga Prasad Chakraborty; Rajesh Kumar Thakur; Nirmal Kumar Bera (Asian Journal of Medical Sciences, 2024)
Background: Epilepsy and psychogenic non-epileptic seizures (PNES) are both common disease entities and psychiatric comorbidities are also high among the sufferers. Studies on the comparison of the levels of comorbidities between the two groups are few in number. Aims and Objectives: The aims of this study were to investigate different psychiatric disorders like depression, anxiety, social functioning, and quality of life (QoL) in epilepsy and PNES patients and compare them statistically. Materials and Methods: 38 epilepsy and 22 PNES patients were evaluated with clinical history and different tools like the mini international neuropsychiatric interview - 5, Beck’s Depression Inventory - 2,state and trait anxiety inventory, Social and Occupational functioning scale for epilepsy and QoL in epilepsy - 31 questionnaire. Comparisons were made between the groups regarding sociodemographic data, scores on different aspects of psychiatric disorders, social functioning, and QoL. Results: The majority in the epilepsy group were males, and in the PNES group were females, while younger age group predominates in both groups. There was a high prevalence of depression and anxiety in both groups, while PNES subjects had significantly higher depression and trait anxiety scores. Social and occupational functions were comparable in the two groups, but QoL indexes were significantly worse in the PNES group. Conclusion: Findings in this study indicate that psychiatric comorbidities like depression and anxiety disorders are much more common among patients with epilepsy and PNES. Occurrence of depression is even higher among patients with PNES. Both epilepsy/PNES and these psychiatric comorbidities affect Socio-occupational functions and their QoL. Thus, it is very important to look for these psychiatric comorbidities and QoL in these patients and implement proper management protocols to improve their mental health as well as their QoL.